Reading Comprehension: A Study on the Correlation between Grammar and Logic - Marina Udin (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2018)
This study aims to correlate the correlation between grammar and logic in reading ability. This research is a quantitative research using ex-post facto design. The population and samples are taken from the second semester English language study program, amounting to 15 people. Data was collected using tests; there were two tests, namely grammar tests and logic tests, and questionnaires. Data were analyzed using statistics (SPSS) version 16.0. The test results show that their grammar and logic correlation coefficients are -0,028 at a significant level of 0.922. This means that the two variables have a negative correlation, because the value of the result of the correlation between grammar and logic is -0.028 which means <0.05. There is a correlation between grammar and logic, but the negative correlation means that the student's grammar value is higher than the logic value.